2015
DOI: 10.3892/mco.2015.526
|View full text |Cite
|
Sign up to set email alerts
|

MYC is expressed in the stromal and epithelial cells of primary breast carcinoma and paired nodal metastases

Abstract: Abstract. The MYC oncogene is directly involved in the proliferation, metabolism, progression and distant metastasis of breast cancer. Since metastatic spread to the lymph nodes is often the first indication of propensity for metastatic dissemination, the MYC status in nodal disease may represent a decision-making variable. However, the analysis of MYC expression in stromal cells, namely cancer-associated fibroblasts (CAFs), which are known to play a critical role in cancer progression, remains poorly reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the past 20 years, several reports suggest that TAMs are critical players in regulating the “angiogenic switch” and are essential in stimulating tumor angiogenesis and progression [ 29 , 79 , 80 ]. It has also been noted that the up-regulation of MYC was found in cancer-associated fibroblasts (CAFs) and that CAFs can promote tumor angiogenesis by secreting cytokines that recruit endothelial cells to form tumor-associated blood vessels—suggesting that MYC is also important in the regulation of CAFs within tumor microenvironment [ 81 , 82 , 83 ]. Hypoxia is recognized as a major driver of angiogenesis.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 20 years, several reports suggest that TAMs are critical players in regulating the “angiogenic switch” and are essential in stimulating tumor angiogenesis and progression [ 29 , 79 , 80 ]. It has also been noted that the up-regulation of MYC was found in cancer-associated fibroblasts (CAFs) and that CAFs can promote tumor angiogenesis by secreting cytokines that recruit endothelial cells to form tumor-associated blood vessels—suggesting that MYC is also important in the regulation of CAFs within tumor microenvironment [ 81 , 82 , 83 ]. Hypoxia is recognized as a major driver of angiogenesis.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…This demonstrates that the increased expression of MYC can be linked with nodal metastases. Fibroblasts expressing MYC act locally at metastatic site and help to facilitate colonization by creating a lymphangiogenic microenvironment to support cancer cells’ survival [ 83 , 99 ]. Moreover, MYC directly regulates several genes related to glucose metabolism (such as Lactate dehydrogenase A), and CAFs were reported to have increased expression of glycolytic enzymes.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
See 1 more Smart Citation
“…This enhanced vascular network facilitates cancer cell survival and enables the cells’ rapid proliferation. Emerging evidence indicates that MYC upregulation is not limited to cancer cells but also extends to cancer-associated fibroblasts (CAFs) [ 109 ]. CAFs have been shown to play a crucial role in promoting tumor angiogenesis [ 110 , 111 ].…”
Section: Myc As a Regulator Of The Tumor Microenvironment Leading To ...mentioning
confidence: 99%
“… 62 c-Myc expression in CAFs has been shown to promote the secretion of cytokines that induce the formation of blood vessels by recruiting endothelial cells. 63 There are other c-Myc induced proteins and non-coding RNAs that promote angiogenesis. The study of Ciribilli and Borlak 64 identified 25 novel target genes of c-Myc in a transgenic mouse model of lung cancer, some of which, such as G-protein couple receptor Adora2B, induced angiogenesis by either inducing VEGF or downregulating negative regulators of HIF-1 α .…”
Section: C-myc Mediated Resistance Mechanismsmentioning
confidence: 99%